A study on confectionery product distributor’s activities compared with compliance issues and standards set by Nestlé Bangladesh Ltd.' - Farhan, Nadeem (Brac University, 2021)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2019.